Philipp van Limborch and John Locke. The Arminian Influence on Locke’s Theology and Theory of Toleration - Svensson, Manfred (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
The aim of this essay is to present an analysis of the way in which the principal theologicalwork of Dutch Arminianism of seventeenth-century, Theologia Christiana of Philipp van Limborchinfluenced John Locke. The aim is two fold: to show, on the one hand, the influence of van Limborch’stheology on Locke’s theological reflections, on the other hand, the way in which Locke’s understandingof tolerance is embedded in this kind of theology.
Keywords: Locke; van Limborch; tolerance; theology; necessary-non necessary; adiaphora